Perovskite-based photovoltaic cell and preparation method thereof
By adding partially neutralized polyacrylic acid to the photoactive layer of perovskite photovoltaic cells, the problems of humidity sensitivity and poor crystalline phase stacking of perovskite photovoltaic cells are solved, achieving high efficiency and good mechanical properties, and are suitable for For large area applications.
Patent Information
- Application Number
- CN202380045825.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-10
- Filing Date
- 2023-06-08
- Publication Date
- 2025-01-24
AI Technical Summary
Existing perovskite-based photovoltaic cells have shortcomings in the problems of high sensitivity of the aerodynamic factors such as humidity and poor crystal phase accumulation, which affects their performance and scale-up applications.
Part of the neutralized polyacryonic acid is introduced in the photocopy activity layer of perovskite, which accounts for more than 3%of the total weight of the precursor of the perovskite, preferably 4%to 15%to improve the particle size and stacking structure of the perovskite crystal. And enhance the mechanical elasticity and humidity of photovoltaic batteries.
The high -power conversion efficiency (PCE) of the perovskite photovoltaic battery exceeds 10%, and the single -step deposition osteotic optical activity layer is suitable for the structure of large -scale photovoltaic batteries without using non -solvents. Optical properties.
Smart Images

Figure CN119366284A_ABST
Abstract
Description
[0001] The present invention relates to perovskite-based photovoltaic cells (or solar cells).
[0002] More specifically, the present invention relates to perovskite-based photovoltaic cells (or solar cells), wherein the perovskite photoactive layer comprises at least one partially neutralized polyacrylic acid in an amount greater than or equal to 3 wt. %, preferably from 4 wt. % to 15 wt. %, more preferably from 4.5 wt. % to 12 wt. %, relative to the total weight of the perovskite precursor.
[0003] The perovskite-based photovoltaic cell (or solar cell) can be advantageously used in various applications where it is necessary to generate electrical energy by utilizing light energy, in particular solar radiation energy, such as: building integrated photovoltaic systems (building integrated photovoltaics - BIPV); photovoltaic windows; greenhouses; photobioreactors; noise barriers; lighting engineering; design; advertising; automotive industry. The perovskite-based photovoltaic cell (or solar cell) can be used both in a stand-alone mode and in a modular system.
[0004] The present invention also relates to a method for preparing the perovskite-based photovoltaic cell (or solar cell).
[0005] Another object of the present invention is also a composition comprising at least one perovskite and at least one partially neutralized polyacrylic acid in an amount greater than or equal to 3% by weight, preferably from 4% to 15% by weight, more preferably from 4.5% to 12% by weight, based on the total weight of the perovskite precursor.
[0006] Photovoltaic cells (or solar cells) are devices capable of converting light radiation energy into electrical energy. Currently, most photovoltaic cells (or solar cells) that can be used for practical applications make use of the chemical-physical properties of inorganic type photoactive materials, especially high-purity crystalline silicon. However, although the photovoltaic cells (or solar cells) provide interesting performances, especially in terms of efficiency and durability, they also show some disadvantages. For example, the hardness and weight of the photovoltaic cells (or solar cells) based on silicon often make it necessary to install special frames for their positioning, and in fact severely limit their field of use.
[0007] Some of the above-mentioned disadvantages can be overcome by using photovoltaic cells (or solar cells) based on organic polymers (organic photovoltaics - OPV) or based on perovskites (perovskite solar cells - PSC).
[0008] In particular, photovoltaic cells (or solar cells) based on perovskites (perovskite solar cells - PSCs) have rapidly emerged in recent years as a promising alternative, since they combine a high power conversion efficiency (PCE), which has currently reached a certified value of 25.5%, with a series of typical features of photovoltaic cells (or solar cells) based on thin films of organic polymers (organic photovoltaics - OPVs), such as the lightness, flexibility and simplicity of the manufacturing process starting from a suitable mixture of various precursors, which can allow the production of photovoltaic cells (or solar cells) under mild conditions and at sustainable costs by means of a well-known unified printing method (also continuous).
[0009] However, perovskite-based photovoltaic cells (or solar cells) (perovskite solar cells - PSCs) may also have some disadvantages, such as the high sensitivity of perovskites to atmospheric factors (especially humidity), non-optimal stacking of perovskite crystalline phases (which has a negative impact on charge transport).
[0010] To address the above-mentioned shortcomings, many research teams have developed various techniques for constructing perovskite-based photovoltaic cells (or solar cells) (perovskite solar cells - PSCs), which include, for example, the use of polymer additives within the perovskite photoactive layer.
[0011] In the past few years, many hydrophobic and hydrophilic polymers with thermoplastic and elastic characteristics have been adopted, and the results have been summarized in the review "Solar RRL" (2021) by Kim K. et al., Volume 5, Page 2000783, doi.org / 10.1002 / solr.202000783., which describes the role and contribution of polymer additives in perovskite-based solar cells. In particular, the use of polymers or polymeric materials as additives is disclosed to promote the nucleation and crystallization of the perovskite photoactive layer, thereby increasing the particle size of the perovskite crystals. The polymers allow good passivation of defects present on the edges of the perovskite crystals due to their high molecular weight. In addition, the polymers can lead to an increase in their particle size by limiting the growth rate of the perovskite crystals, thereby allowing better stacking between them. In addition, some polymers act as charge carrier materials in the interface layer, thereby effectively separating charge carriers and reducing charge recombination. In addition, some hydrophobic polymers can protect the perovskite photoactive layer from moisture, while elastic polymers can contribute to the mechanical elasticity of the perovskite photoactive layer through cross-linking and self-healing.
[0012] Ko Y. et al. reported in Synthetic Metals (2019), Vol. 249, pp. 47-51, a method for preparing perovskite-based solar cells with the following arrangement: c-TiO2 / MAPbI3-x Cl x -PMMA / PTAA / Au. The method consists in depositing a layer of a mixture of PbI2 and PbCl2, followed by immersing the matrix obtained in a solution containing MAI (20 mg / ml) and PMMA (the amount of PMMA is very low, about 1 / 4000 relative to the weight of MAI), achieving the formation of a perovskite crystalline phase in the presence of PMMA. The method allows obtaining perovskite-based solar cells with a power conversion efficiency (PCE) equal to 15.3%, thanks to the improvement in the charge transport capacity associated with the improvement in the morphology and crystallinity of the perovskite photoactive layer. However, it is believed that the above-mentioned manufacturing method may be very complicated and difficult to use in the scale-up phase of the construction of large-area photovoltaic cells (or solar cells), since it provides for the two-step formation of the perovskite photoactive layer. In addition, since it is not possible to determine the amount of PMMA effectively incorporated in the perovskite photoactive layer using the above-mentioned method, the method is likely not to guarantee a good reproducibility of the results.
[0013] Saraf R. et al. reported in "ACS Applied Energy Materials" (2019), Vol. 2, pp. 2214-2222 a method for manufacturing perovskite-based solar cells with the following arrangement: ZnO / MAPbI3-PS / spiro-OMeTAD / Au. The method involves depositing a perovskite photoactive layer from equimolar PbI2 and MAI solutions containing different amounts of polystyrene (PS) (from 0.5 wt. % to 14 wt. %). Operating under the most favorable conditions (i.e., PS = 1 wt. %), the method allows obtaining perovskite-based solar cells with a power conversion efficiency (PCE) equal to 12.27%, thanks to the increase in the size of the grain size of the perovskite crystals determined by better crystallization kinetics. However, it is believed that the above-mentioned manufacturing method is not suitable for use in the scale-up stage of large-area photovoltaic cell (or solar cell) construction because it provides a two-step process of 200°C annealing step for forming the ZnO layer and adding a non-solvent for forming the perovskite photoactive layer: this two-step process, in addition to complicating the perovskite film deposition process, also produces poor reproducibility. In addition, according to the authors' reports, it seems that the polystyrene solution in the presence of PbI2 is unstable and leads to the formation of partially cross-linked polymer materials, and therefore, it is believed that this phenomenon will lead to significant non-reproducibility in the performance of the photovoltaic cells (or solar cells) obtained therefrom.
[0014] Kim et al. reported in Journal of Materials Chemistry A (2019), Vol. 7, pp. 20832-20839 a method for fabricating perovskite-based solar cells having the following arrangement: TiO2 / FAx MA 1-x PbI3-PDMS / spiro-OMeTAD / Au. The method includes starting from a DMF solution containing PbI2, MAI, FAI and DMSO (molar ratio of 1:0.85:0.15:1) and depositing a perovskite photoactive layer by spin coating. During the spin coating step, 0.3 ml of a toluene solution containing different weights of polydimethylsiloxane (PDMS) is added to the matrix. By operating under the most favorable conditions (i.e. PDMS = 0.03 wt. % in toluene), a perovskite-based solar cell with a power conversion efficiency (PCE) equal to 15.44% is obtained due to the acquisition of perovskite crystals with more regular shapes and narrower size distribution. However, it is believed that the above method is not suitable for use in the scale-up stage of constructing large-area photovoltaic cells (or solar cells) because it provides a two-step method of annealing steps at 500°C for forming the TiO2 layer and adding a non-solvent for forming the perovskite photoactive layer. Furthermore, since the amount of PDMS effectively incorporated into the perovskite photoactive layer cannot be determined using the above method, the method is likely not to guarantee good reproducibility of the results.
[0015] Liu G. et al. reported in "ACS Applied Materials & Interfaces" (2020), Vol. 2, p. 14049 a method for manufacturing a perovskite-based solar cell having the following arrangement: PEDOT:PSS / FASnI3-EVA / PCBM-BTP / Ag. The method comprises forming a perovskite photoactive layer by spin coating a DMSO / DMF solution (1 / 4, v / v) containing equimolar amounts of SnI2 and FAI. During the spin coating step, a chlorobenzene solution containing different weight percentages of polyethylene vinyl acetate (EVA) was added to the matrix. Operating under the most favorable conditions (ie, EVA = 2 mg / ml in chlorobenzene), a perovskite-based solar cell with a power conversion efficiency (PCE) equal to 7.72% was obtained due to the better quality of the perovskite photoactive layer and the increased perovskite crystal size. However, it is believed that the above method is not suitable for use in the scale-up stage of constructing large-area photovoltaic cells (or solar cells) because it includes a two-step process of adding a non-solvent for forming the perovskite photoactive layer. In addition, since the amount of EVA actually incorporated into the perovskite photoactive layer cannot be determined using the above method, the method is likely to fail to ensure good reproducibility of the results.
[0016] Xue Q. et al. report in "RSC Advances" (2015), Vol. 7, pp. 775-783 a method for manufacturing perovskite-based solar cells with the following arrangement: PEDOT:PSS / MAPbI3-PEOXA / PCBM / Al. The above-reported method (on the manufacture of perovskite-based solar cells and on the manufacture of the photoactive layer) is not reported in detail: however, the authors claim that the results obtained strongly depend on the type of solvent used to dissolve the perovskite precursor and the amount of poly(2-ethyl-2-oxazoline) (PEOXA) used. By operating under the most favorable conditions (i.e., γ-butyrolactone (GBL) as solvent and containing 1.5 wt.% of PEOXA), perovskite-based solar cells with a power conversion efficiency (PCE) equal to 6.16% are obtained due to better control of the crystallization process and the morphology of the perovskite photoactive layer.
[0017] Guo Y. et al. reported in "Advanced Energy Materials" (2016), Vol. 6, 1502317, a method for manufacturing perovskite-based solar cells with the following arrangement: PEDOT:PSS / MAPbIxCl 3-x -PVP / PCBM-PEIE / Ag. The method involves preparing a perovskite photoactive layer by spin coating a DMF solution containing the following perovskite precursors: MAI, PbI2 and PbCl2 (molar ratio of 4:1:1) and different amounts (0 wt%-6 wt%) of polyvinylpyrrolidone (PVP). By operating under the most favorable conditions (i.e. 3 wt% PVP), a perovskite-based solar cell with a power conversion efficiency (PCE) equal to 7.91% was obtained due to the improvement of the size and morphology of the perovskite crystals, and a significant improvement in the thermal stability of the perovskite photoactive layer was also obtained.
[0018] From the above it is evident the importance of discovering other polymers capable of being used as additives in perovskite photoactive layers, which allow obtaining perovskite-based photovoltaic cells (or solar cells) (perovskite solar cells - PSCs) capable of having a good power conversion efficiency (PCE), as well as methods for constructing them suitable for use in the scale-up phase of constructing large-area photovoltaic cells (or solar cells).
[0019] The problem faced by the Applicant is therefore to find a perovskite-based photovoltaic cell (or solar cell) capable of having a good power conversion efficiency (PCE), and a method for constructing the same which is suitable for use in the scale-up phase of constructing large-area photovoltaic cells (or solar cells).
[0020] The applicant has now discovered a photovoltaic cell (or solar cell) based on perovskite and a method for its construction, wherein the perovskite photoactive layer comprises at least one partially neutralized polyacrylic acid in an amount greater than or equal to 3 wt. %, preferably 4 wt. % to 15 wt. %, more preferably 4.5 wt. % to 12 wt. %, relative to the total weight of the perovskite precursor, the cell being able to have a good power conversion efficiency (PCE) (i.e. PCE>10%), the method depositing the perovskite photoactive layer in a single step without the use of a non-solvent and at a deposition temperature of each layer below 120° C. Therefore, the method is suitable for use in the scale-up phase of constructing large-area photovoltaic cells (or solar cells). In addition, the perovskite-based photovoltaic cell (or solar cell) is able to maintain good optoelectronic properties, i.e. good values of FF (fill factor), Voc (open circuit voltage), Jsc (short circuit photocurrent). The perovskite-based photovoltaic cell (or solar cell) can be advantageously used in various applications where it is necessary to generate electrical energy by utilizing light energy, in particular solar radiation energy, such as: building integrated photovoltaic systems (building integrated photovoltaics - BIPV); photovoltaic windows; greenhouses; photobioreactors; noise barriers; lighting engineering; design; advertising; automotive industry. In addition, the perovskite-based photovoltaic cell (or solar cell) can be used both in a stand-alone mode and in a modular system.
[0021] The present invention therefore relates to photovoltaic cells (or solar cells) based on perovskites, wherein the photoactive layer of the perovskite comprises at least one partially neutralized polyacrylic acid in an amount greater than or equal to 3% by weight, preferably from 4% to 15% by weight, more preferably from 4.5% to 12% by weight, relative to the total weight of the perovskite precursor.
[0022] For the purposes of the present description and of the following claims, the definitions of numerical ranges always include the endpoints, unless stated otherwise.
[0023] For the purposes of this specification and the claims that follow, the term "comprising" also encompasses the terms "consisting essentially of" or "consisting of.
[0024] According to a preferred embodiment of the present invention, the perovskite may be selected from, for example, an organometallic trihalide having the general formula ABX3, wherein:
[0025] -A represents a monovalent organic cation, for example, methylammonium (CH3NH3 + ), formamidinium [CH(NH2)2 + ], n-butylammonium (C4H 12 NH3 + ), tetrabutylammonium (C 16 H 36 N+ ) or a mixture thereof; or A represents a monovalent inorganic cation, such as a cesium ion (Cs + ), rubidium ion (Rb + ), potassium ion (K + ), lithium ion (Li + ), sodium ion (Na + ), copper ions (Cu + ), silver ions (Ag + ) or a mixture thereof; or a mixture thereof;
[0026] -B represents a divalent metal cation, such as lead ion (Pb 2+ ), tin ions (Sn 2+ ) or a mixture thereof;
[0027] -X represents a halogen anion, such as an iodide ion (I - ), chloride ion (Cl - ), bromide ion (Br - ) or a mixture thereof.
[0028] According to another preferred embodiment of the present invention, the perovskite can be selected from the following: methylammonium lead iodide (CH3NH3PbI3), methylammonium lead bromide (CH3NH3PbBr3), methylammonium lead chloride (CH3NH3PbCl3), methylammonium lead bromide iodide (CH3NH3PbI x Br 3-x ), methylammonium lead chloride iodide (CH3NH3PbI x Cl 3-x ), formamidine lead iodide [CH(NH2)2PbI3], formamidine lead bromide [CH(NH2)2PbBr3], formamidine lead chloride [CH(NH2)2PbCl3], formamidine lead bromide iodide [CH(NH2)2PbI x Br 3-x ]、Formamidine lead chloride iodide [CH(NH2)2PbI x Cl 3-x ]、Methylammonium formamidinium lead iodide [(CH3NH3) x (CH(NH2)2) 1-x PbI3], methylammonium formamidinium lead bromide [(CH3NH3) x (CH(NH2)2) 1-x PbBr3], methylammonium formamidinium lead chloride [(CH3NH3) x (CH(NH2)2) 1-x PbCl3], methylammonium formamidinium chloride lead iodide [(CH3NH3) x (CH(NH2)2) 1-x PbI 3-yCl y ], methylammonium formamidinium bromide lead iodide [(CH3NH3) x (CH(NH2)2) 1-x PbI 3-y Br y ], n-butylammonium lead iodide (C4H 12 NH3PbI3), tetrabutylammonium lead iodide (C 16 H 36 NPbI3), n-butylammonium lead bromide (C4H 12 NH3PbBr3), tetrabutylammonium lead bromide (C 16 H 36 NPbBr3), cesium lead iodide (CsPbI3), rubidium lead iodide (RbPbI3), potassium lead iodide (KPbI3), methylammonium cesium lead iodide [Cs x (CH3NH3) 1-x PbI3], methylammonium potassium lead iodide [K x (CH3NH3) 1-x PbI3], methylammonium chloride cesium lead iodide [Cs x (CH3NH3) 1-x PbI 3-y Cl y ], cesium lead formamidine iodide [Cs x (CH(NH2)2) 1-x PbI3], cesium lead bromide [Cs x (CH(NH2)2) 1-x PbBr3], cesium lead iodide [Cs x (CH(NH2)2) 1-x PbI 3-y Cl y ], methylammonium tin iodide (CH3NH3SnI3), methylammonium tin bromide (CH3NH3SnBr3), methylammonium tin bromide iodide (CH3NH3SnI x Br 3-x ), formamidine tin iodide [CH(NH2)2SnI3], formamidine tin bromide iodide (CH3NH3SnI x Br 3-x ), n-butylammoniumtiniodide (C4H 12 NH3SnI3), tetrabutylammoniumtin iodide (C 16 H 36 NSnI3), n-butylammoniumtin bromide (C4H 12 NH3SnBr3), tetrabutylammoniumtin bromide (C 16 H 36 NSnBr3), methylammonium tin lead iodide (CH3NH3Sn x Pb1-x I3), tin lead iodide [CH(NH2)2Sn x Pb 1-x I3], or a mixture thereof. Preferably, methylammonium lead iodide (CH3NH3PbI3), formamidine lead iodide [CH(NH2)2PbI3], methylammonium formamidine lead iodide chloride [(CH3NH3) x (CH(NH2)2) 1-x PbI 3-y Cl y ], methylammonium chloride cesium lead iodide [Cs x (CH3NH3) 1-x PbI 3-y Cl y ], cesium lead iodide chloride [Cs x (CH(NH2)2) 1-x PbI 3-y Cl y ]. Even more preferred is methylammonium lead iodide (CH3NH3PbI3).
[0029] According to a preferred embodiment of the present invention, the partially neutralized polyacrylic acid has the general formula (I):
[0030]
[0031] in:
[0032] - n and m are integers, and:
[0033] - the sum n+m is from 10 to 60000, preferably from 15 to 15000, more preferably from 20 to 6000;
[0034] - the ratio n:m is from 99:1 to 1:99, preferably from 98:2 to 20:80, more preferably from 95:5 to 50:50;
[0035] -M + represents a monovalent metal cation selected from alkali metals, such as lithium ion (Li + ), sodium ion (Na + ), potassium ion (K + ), rubidium ion (Rb + ), cesium ion (Cs + ), preferably lithium ion (Li + ), potassium ion (K + ), rubidium ion (Rb + ), cesium ion (Cs + ), more preferably potassium ion (K + ), cesium ion (Cs + ); or selected from other monovalent metals, such as copper ions (Cu+ ), silver ions (Ag + ), gold ions (Au + ), mercury ion (Hg + ), thallium ion (Tl + ), preferably copper ions (Cu + ), silver ions (Ag + );
[0036] - or M + represents a monovalent cation having the general formula (II):
[0037]
[0038] in:
[0039] -E represents a nitrogen atom or a phosphorus atom, preferably a nitrogen atom;
[0040] - R1, R2, R3 and R4 are the same or different from each other and represent a hydrogen atom; or are selected from C1-C 20 , preferably C1-C 12 A straight or branched, saturated or unsaturated, optionally heteroatom-containing alkyl group; an optionally substituted aryl group; an optionally substituted heteroaryl group; an optionally substituted cycloalkyl group; an optionally substituted heterocyclic group;
[0041] - or R1 and R2, and / or R2 and R3, and / or R3 and R4, and / or R4 and R1, may be bonded together so as to form, together with the other atoms to which they are bonded, a saturated, unsaturated or aromatic ring containing 2 to 12 carbon atoms, optionally substituted by: a linear or branched, saturated or unsaturated C1-C 20 , preferably C1-C 12 , an alkyl group optionally containing heteroatoms, an optionally substituted aryl group, an optionally substituted heteroaryl group, an optionally substituted cycloalkyl group, an optionally substituted heterocyclic group, a trialkyl-silyl group or a triaryl-silyl group, a dialkyl-amino group or a diaryl-amino group, a dialkyl-phosphinyl group or a diaryl-phosphinyl group, a C1-C 20 , preferably C2-C 10 , linear or branched, saturated or unsaturated alkoxy, optionally substituted aryloxy, optionally substituted thioalkoxy or thioaryloxy, cyano, the ring optionally containing heteroatoms such as oxygen, sulfur, nitrogen, silicon, phosphorus, selenium, preferably oxygen, nitrogen;
[0042] - or M + represents a monovalent cation having the general formula (III):
[0043]
[0044] in:
[0045] -R5 represents a hydrogen atom; or represents a halogen atom, such as fluorine, chlorine, bromine, iodine, preferably fluorine, chlorine; or is selected from a linear or branched, saturated or unsaturated C1-C 20 , preferably C1-C 12 , optionally containing heteroatoms alkyl; optionally substituted aryl; optionally substituted heteroaryl; optionally substituted cycloalkyl; optionally substituted heterocyclic group; preferably R5 is hydrogen or methyl;
[0046] - R6, R7, R8 and R9 are the same or different from each other and represent a hydrogen atom; or are selected from a linear or branched, saturated or unsaturated C1-C 20 , preferably C1-C 12 , an alkyl group optionally containing a heteroatom; an optionally substituted aryl group; an optionally substituted heteroaryl group; an optionally substituted cycloalkyl group; an optionally substituted heterocyclic group;
[0047] - or R7 and R8, and / or R9 and R 10 may be bonded together so as to form, together with the other atoms to which they are bonded, a saturated, unsaturated or aromatic ring containing 2 to 12 carbon atoms, optionally substituted by: a straight or branched, saturated or unsaturated C1-C 20 , an alkyl group optionally containing heteroatoms, an optionally substituted aryl group, an optionally substituted heteroaryl group, an optionally substituted cycloalkyl group, an optionally substituted heterocyclic group, a trialkyl-silyl group or a triaryl-silyl group, a dialkyl-amino group or a diaryl-amino group, a dialkyl-phosphinyl group or a diaryl-phosphinyl group, a C1-C 20 , preferably C2-C 10 , a linear or branched, saturated or unsaturated alkoxy group, an optionally substituted aryloxy group, an optionally substituted thioalkoxy group or thioaryloxy group, a cyano group, the ring optionally containing heteroatoms, such as oxygen, sulfur, nitrogen, silicon, phosphorus, selenium, preferably oxygen, nitrogen; preferably, R6, R7, R8 and R9 represent hydrogen atoms.
[0048] For the purposes of this specification and the claims that follow, the term “C1-C 20 "Alkyl" means a straight or branched, saturated or unsaturated alkyl group having 1 to 20 carbon atoms. 20 Specific examples of the alkyl group are: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, pentyl, hexyl, heptyl, octyl, 2-ethylheptyl, 2-ethylhexyl, 2-butenyl, 2-pentenyl, 2-ethyl-3-hexenyl, 3-octenyl, 1-methyl-4-hexenyl, 2-butyl-3-hexenyl.
[0049] For the purposes of this specification and the claims that follow, the term "C1-C1 optionally containing heteroatoms" 20"Alkyl" means a straight or branched, saturated or unsaturated alkyl group having 1 to 20 carbon atoms, wherein at least one hydrogen atom is substituted by a heteroatom selected from the group consisting of halogen, such as fluorine, chlorine, bromine, preferably fluorine; nitrogen; sulfur; oxygen. The C1-C 20 Specific examples of the alkyl group are fluoromethyl, difluoromethyl, trifluoromethyl, trichloromethyl, 2,2,2-trifluoroethyl, 2,2,2-trichloroethyl, 2,2,3,3-tetrafluoropropyl, 2,2,3,3,3-pentafluoropropyl, perfluoropentyl, perfluorooctyl, perfluorodecyl, ethyl-2-methoxy, propyl-3-ethoxy, butyl-2-thiomethoxy, hexyl-4-amino, hexyl-3-N,N'-dimethylamino, methyl-N,N'-dioctylamino, 2-methyl-hexyl-4-amino.
[0050] For the purpose of this specification and the subsequent claims, the term "aryl" means an aromatic carbocyclic group containing 6 to 60 carbon atoms. The aryl group may be optionally substituted by one or more groups selected from the following groups, which may be the same or different from each other: halogen atoms, such as fluorine, chlorine, bromine, preferably fluorine; hydroxyl; C1-C 12 Alkyl; C1-C 12 Alkoxy; C1-C 12 Thioalkoxy; C3-C 24 trialkylsilyl; polyethyleneoxy; cyano; amino; C1-C 12 Mono- or di-alkylamino; nitro. Specific examples of aryl are: phenyl, methylphenyl, mesityl, methoxyphenyl, hydroxyphenyl, phenoxyphenyl, fluorophenyl, pentafluorophenyl, chlorophenyl, bromophenyl, nitrophenyl, dimethylaminophenyl, naphthyl, phenylnaphthyl, phenanthrene, anthracene.
[0051] For the purpose of this specification and the subsequent claims, the term "heteroaryl" refers to an aromatic, five- or six-atom heterocyclic radical, which may also be a benzocondensate or a heterobicyclic ring, containing 4 to 60 carbon atoms and 1 to 4 heteroatoms selected from nitrogen, oxygen, sulfur, silicon, selenium, phosphorus. The heteroaryl radical may be optionally substituted by one or more groups selected from the following, which may be identical or different from each other: halogen atoms, such as fluorine, chlorine, bromine, preferably fluorine; hydroxyl; C1-C 12 Alkyl; C1-C 12 Alkoxy; C1-C 12 Thioalkoxy; C3-C 24 trialkylsilyl; polyethyleneoxy; cyano; amino; C1-C 12Specific examples of heteroaryl groups are: pyridine, picoline, methoxypyridine, phenylpyridine, fluoropyridine, pyrimidine, pyridazine, pyrazine, triazine, tetrazine, quinoline, quinoxaline, quinazoline, furan, thiophene, hexylthiophene, bromothiophene, dibromothiophene, pyrrole, oxazole, thiazole, isoxazole, isothiazole, oxadiazole, thiadiazole, pyrazole, imidazole, triazole, tetrazole, indole, benzofuran, benzothiophene, benzoxazole, benzothiazole, benzooxadiazole, benzothiadiazole, benzopyrazole, benzimidazole, benzotriazole, triazole pyrazole, triazole pyrimidine, coumarin.
[0052] For the purpose of this specification and the subsequent claims, the term "cycloalkyl" refers to a cycloalkyl group having 3 to 60 carbon atoms. The cycloalkyl group may be optionally substituted by one or more groups selected from the following groups, which may be identical or different from each other: halogen atoms, such as fluorine, chlorine, bromine, preferably fluorine; hydroxyl; C1-C 12 Alkyl; C1-C 12 Alkoxy; C1-C 12 Thioalkoxy; C3-C 24 trialkylsilyl; polyethyleneoxy; cyano; amino; C1-C 12 Mono- or di-alkylamino; nitro. Specific examples of cycloalkyl are: cyclopropyl, 2,2-difluorocyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, methylcyclohexyl, methoxycyclohexyl, fluorocyclohexyl, phenylcyclohexyl, decalin, abiethyl.
[0053] For the purpose of this specification and the subsequent claims, the term "heterocyclic group" means a saturated or unsaturated ring having 3 to 12 atoms, which contains at least one heteroatom selected from nitrogen, oxygen, sulfur, silicon, selenium, phosphorus, optionally fused to other aromatic or non-aromatic rings. The heterocyclic group may be optionally substituted by one or more groups selected from the following, which may be identical or different from each other: halogen atoms, such as fluorine, chlorine, bromine, preferably fluorine; hydroxyl; C1-C 12 Alkyl; C1-C 12 Alkoxy; C1-C 12 Thioalkoxy; C3-C 24 trialkylsilyl; polyethyleneoxy; cyano; amino; C1-C 12 Mono- or di-alkylamino; nitro. Specific examples of heterocyclic groups are: pyrrolidine, methoxypyrrolidine, piperidine, fluoropiperidine, methylpiperidine, dihydropyridine, piperazine, morpholine, thiazine, indoline, phenylindoline, 2-ketoazetidine, diketopiperazine, tetrahydrofuran, tetrahydrothiophene.
[0054] For the purpose of the present description and the subsequent claims, the term "ring" means a system comprising a ring containing from 1 to 12 carbon atoms, optionally containing heteroatoms selected from nitrogen, oxygen, sulfur, silicon, selenium, phosphorus. Specific examples of rings are: toluene, benzonitrile, cycloheptatriene, cyclooctadiene, pyridine, piperidine, tetrahydrofuran, thiadiazole, pyrrole, thiophene, selenophene, tert-butylpyridine.
[0055] For the purposes of this specification and the claims that follow, the term "trialkyl- or triaryl-silyl" means a group comprising three C1-C 12 Alkyl or three C6-C 24 A group of silicon atoms bonded to an aryl group or a combination thereof. Specific examples of trialkyl- or triaryl-silyl groups are: trimethylsilane, triethylsilane, trihexylsilane, tridodecylsilane, dimethyldodecylsilane, triphenylsilane, methyldiphenylsilane, dimethylnaphthylsilane.
[0056] For the purposes of this specification and the claims that follow, the term "dialkyl- or diaryl-amino" means a group containing a nitrogen atom, two C1-C 12 Alkyl, or two C6-C 24 Aryl, or a combination thereof is attached to the nitrogen atom. Specific examples of dialkyl- or diaryl-amino groups are: dimethylamine, diethylamine, dibutylamine, diisobutylamine, diphenylamine, methylaniline, dibenzylamine, ditoluidine, dinaphthylamine.
[0057] For the purposes of this specification and the claims that follow, the term "dialkyl- or diaryl-phosphino" means a group containing a phosphorus atom, two C1-C 12 Alkyl, or two C6-C 24 An aryl group, or a combination thereof is bonded to the phosphorus atom. Specific examples of dialkyl- or diaryl-phosphino groups are: dimethylphosphine, diethylphosphine, dibutylphosphine, diphenylphosphine, methylphenylphosphine, dinaphthylphosphine.
[0058] For the purposes of this specification and the claims that follow, the term “C1-C 20 "Alkoxy" means a group containing an oxygen atom, a straight or branched C1-C 20 The alkyl group is bonded to the oxygen atom. 20 Specific examples of the alkoxy group are methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, pentyloxy, hexyloxy, heptyloxy, octyloxy, nonyloxy, decyloxy, dodecyloxy.
[0059] For the purposes of this specification and the claims that follow, the term "aryloxy" refers to a group containing an oxygen atom, a C6-C 24The aryl group is bonded to the oxygen atom. The aryloxy group may be optionally substituted by one or more groups selected from the following groups, which may be the same or different from each other: a halogen atom, such as fluorine, chlorine, bromine, preferably fluorine; a hydroxyl group; a C1-C 12 Alkyl; C1-C 12 Alkoxy; C1-C 12 Thioalkoxy; C3-C 24 trialkylsilyl; cyano; amino; C1-C 12 mono- or di-alkylamino; nitro. Specific examples of aryloxy are: phenoxy, p-methylphenoxy, p-fluorophenoxy, o-butylphenoxy, naphthyloxy, anthracenyloxy.
[0060] For the purposes of this specification and the claims that follow, the term "thioalkoxy or thioaryloxy" means a group containing a sulfur atom, C1-C 12 Alkoxy or C6-C 24 The thioalkoxy or thioaryloxy group may be optionally substituted by one or more groups selected from the following groups, which may be the same or different from each other: a halogen atom, such as fluorine, chlorine, bromine, preferably fluorine; a hydroxyl group; a C1-C 12 Alkyl; C1-C 12 Alkoxy; C1-C 12 Thioalkoxy; C3-C 24 trialkylsilyl; cyano; amino; C1-C 12 Specific examples of the thioalkoxy or thioaryloxy groups are thiomethoxy, thioethoxy, thiopropoxy, thiobutoxy, thioisobutoxy, 2-ethylthiohexyl, thiophenoxy, p-methylthiophenoxy, p-fluorothiophenoxy, o-butylthiophenoxy, naphthylthiooxy, anthracenylthiooxy.
[0061] According to a preferred embodiment of the present invention, in the partially neutralized polyacrylic acid, free carboxyl groups are present in an amount of 1% to 99%, preferably 20% to 98%, more preferably 50% to 96%, relative to the total amount of carboxyl groups present in the polyacrylic acid.
[0062] The above partially neutralized polyacrylic acid can be obtained according to methods known in the art. For example, the starting polyacrylic acid can be reacted with a carbonate or bicarbonate of an alkali metal selected from the above list in the presence of water for a time necessary to obtain the desired amount of neutralized carboxyl groups: Further details of the preparation of partially neutralized polyacrylic acid are given in the following examples.
[0063] According to a preferred embodiment of the present invention, the weight average molecular weight (M) of the starting polyacrylic acid (ie, not partially neutralized) is w) can be 700Da to 4000000Da, preferably 1000Da to 1000000Da, more preferably 1500Da and 400000Da.
[0064] According to a preferred embodiment of the present invention, the perovskite-based photovoltaic cell (or solar cell) comprises:
[0065] - a glass substrate coated with a transparent conductive oxide layer (transparent conductive oxide—TCO) constituting the anode, typically fluorine-doped tin oxide (SnO2:F) (fluorine-doped tin oxide—FTO) or indium tin oxide (indium tin oxide—ITO);
[0066] - a layer based on a hole transport material (hole transport layer—HTL), preferably a layer of poly[bis(4-butylphenyl)-diphenylbenzidine] (polyTPD);
[0067] - optionally, a layer based on a material for improving wettability, preferably a layer of poly[9,9-bis(3'-(N,N-dimethyl)-N-ethylammonium-propyl-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)] diiodide (PFN-I) or a layer of poly[9,9-bis(3'-(N,N-dimethyl)-N-ethylammonium-propyl-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)] (PFN);
[0068] - a photoactive layer comprising: at least one perovskite, preferably methylammonium lead iodide (CH3NH3PbI3) [methylammonium lead iodide (CH3NH3PbI3) is the most commonly used structure due to its high absorption coefficient throughout the UV and visible spectral range, a band gap equal to 1.57 eV, close to the optimum value for maximizing the conversion efficiency and a considerable diffusion distance (more than 100 nm) for electrons and electron holes (or holes)]; and at least one partially neutralized polyacrylic acid, preferably partially neutralized with cesium or potassium, the amount of free carboxyl groups of which is between 60% and 95%;
[0069] - a layer based on an electron transport material (electron transport layer - ETL), preferably [6,6]-phenyl-C 61 -Methyl butyrate (PC 61 BM) layer;
[0070] - Optionally, a layer based on a hole-blocking material (hole-blocking layer—HBL), preferably a layer of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (Batocuproin—BCP) or ethoxylated polyethyleneimine (PEIE);
[0071] A metallic contact, called back contact, constituting the cathode, preferably a layer of gold, silver or metallic aluminum.
[0072] According to a preferred embodiment of the present invention, the electrical energy generated by the at least one perovskite-based photovoltaic cell (or solar cell) may be transmitted using a wiring system connected to the perovskite-based photovoltaic cell (or solar cell).
[0073] As mentioned above, another object of the present invention is a method for preparing the perovskite-based photovoltaic cell (or solar cell).
[0074] Therefore, another object of the present invention is a method for preparing a photovoltaic cell (or solar cell) based on perovskite, comprising the following steps:
[0075] (a) preparing a glass substrate coated with a transparent conductive oxide layer (transparent conductive oxide-TCO) (anode);
[0076] (b) depositing a layer based on a hole transport material (hole transport layer - HTL) on the substrate obtained in step (a);
[0077] (c) optionally, depositing a layer based on a material for improving wettability on the layer based on a hole transport material (hole transport layer—HTL) obtained in step (b);
[0078] (d) preparing a mixture comprising a perovskite precursor and at least one partially neutralized polyacrylic acid, said partially neutralized polyacrylic acid being present in said mixture in an amount greater than or equal to 3% by weight, preferably from 4% to 15% by weight, more preferably from 4.5% to 12% by weight, relative to the total weight of the perovskite precursor;
[0079] (e) depositing the mixture obtained in step (d) on the layer based on a hole transport material (hole transport layer—HTL) obtained in step (b) or on the layer based on a material for improving wettability obtained in step (c) to obtain a photoactive layer;
[0080] (f) depositing a layer based on an electron transport material (electron transport layer - ETL) on the photoactive layer obtained in step (e);
[0081] (g) optionally, depositing a layer based on a hole blocking material (hole blocking layer - HBL) on the layer based on an electron transport material (electron transport layer - ETL) obtained in step (f);
[0082] (h) depositing a metal contact constituting the cathode, called back contact, on the layer based on an electron transport material (ETL) obtained in step (f) or on the layer based on a hole blocking material (hole blocking layer - HBL) obtained in step (g);
[0083] Wherein said steps (b), (c), (e), (f) and (g) are carried out at a temperature below 120°C, preferably 20°C to 115°C.
[0084] For the purpose of the above-mentioned method, the transparent conductive oxide (transparent conductive oxide-TCO), the layer based on hole transport material (hole transport layer-HTL), the layer based on electron transport material (electron transport layer-ETL), the layer based on material for improving wettability, the layer based on hole blocking material (hole blocking layer-HBL) and the metal contact called back contact are selected from those listed above.
[0085] For the purposes of the above method, the mixture comprising a perovskite precursor and at least one polyacrylic acid comprises:
[0086] - at least one halide selected from the halides of the monovalent organic cations or monovalent inorganic cations listed above, preferably iodide, chloride, bromide, more preferably iodide [such as methylammonium iodide (MAI)(CH3NH3I)], and at least one halide selected from the halides of the above-mentioned divalent metal cations, preferably iodide, chloride, bromide, more preferably iodide [such as lead iodide (PbI2)], as a perovskite precursor;
[0087] at least one partially neutralized polyacrylic acid, preferably partially neutralized with cesium or potassium, the amount of free carboxyl groups of which is between 60% and 95%.
[0088] For the purpose of the above method, steps (b), (c), (e), (f) and (g) can be carried out according to deposition techniques known in the art, such as spin coating, spray coating, inkjet printing, slot coating, gravure printing, screen printing.
[0089] For the purpose of the above method, said step (h) can be carried out according to techniques known in the art, such as evaporation, sputtering, electron beam assisted deposition, sputtering, spin coating, gravure printing, flexographic printing, slot coating.
[0090] As described above, the perovskite-based photovoltaic cell (or solar cell) can be advantageously used in various applications where it is necessary to generate electrical energy by utilizing light energy, especially solar radiation energy, such as: building integrated photovoltaic systems (building integrated photovoltaics-BIPV); photovoltaic windows; greenhouses; photobioreactors; noise barriers; lighting engineering; design; advertising; automotive industry. In addition, the perovskite-based photovoltaic cell (or solar cell) can be used both in a stand-alone mode and in a modular system.
[0091] Therefore, another object of the present invention is the use of the perovskite-based photovoltaic cells (or solar cells) in the following: building integrated photovoltaic systems (building integrated photovoltaics - BIPV); photovoltaic windows; greenhouses; photobioreactors; noise barriers; lighting engineering; design; advertising; automotive industry.
[0092] As mentioned above, another object of the present invention is also a composition comprising at least one perovskite and at least one partially neutralized polyacrylic acid.
[0093] Therefore, another object of the present invention is a composition comprising at least one perovskite and at least one partially neutralized polyacrylic acid in an amount greater than or equal to 3% by weight, preferably ranging from 4% to 15% by weight, more preferably ranging from 4.5% to 12% by weight, relative to the total weight of the perovskite precursor.
[0094] The at least one perovskite and the at least one partially neutralized polyacrylic acid may be selected from those reported above.
[0095] Now we will refer to the following reports Figure 1 The present invention will be described in more detail by way of embodiments.
[0096] Specifically, Figure 1 A cross-sectional view of a perovskite-based photovoltaic cell (or solar cell) (1) is shown, which comprises the following layers: a glass substrate (7) coated with a transparent conductive oxide layer (transparent conductive oxide - TCO) (anode) [e.g., indium tin oxide (ITO) or fluorine-doped tin oxide (SnO2:F) (fluorine-doped tin oxide - FTO)] (2); a layer based on a hole transport material (hole transport layer - HTL) [e.g., poly[bis(4-butylphenyl)-diphenylbenzidine] ( polyTPD)](3); optionally, a layer based on a material for improving wettability, [e.g., poly[9,9-bis(3'-(N,N-dimethyl)-N-ethylammonium-propyl-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)] diiodide (PFN-I), or poly[9,9-bis(3'-(N,N-dimethyl)-N-ethylammonium-propyl-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)] (PFN) ( Figure 1 ); a photoactive layer (4) comprising at least one perovskite [e.g. methylammonium lead iodide (CH3NH3PbI3) and at least one partially neutralized polyacrylic acid (e.g. polyacrylic acid partially neutralized with cesium or potassium, the amount of free carboxyl groups of which is 60% to 95%); a layer based on an electron transport material (electron transport layer - ETL) [e.g. [6,6]-phenyl-C 61 -Methyl butyrate (PC 61 BM)](5a); a layer based on a hole blocking material (hole blocking layer - HBL) [for example, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (Batocuproine-BCP) or ethoxylated polyethyleneimine (PEIE)](5b); a metal contact called back contact constituting the cathode [for example, a layer of gold, silver or metallic aluminum](6).
[0097] In order to better understand the present invention and put it into practice, some illustrative and non-limiting examples of the present invention are given below.
[0098] In the following embodiments, for the sake of simplicity, the term solar cell is used, which should be understood to have the same meaning as a photovoltaic cell.
[0099] Example 1
[0100] Preparation of polyacrylic acid partially neutralized with cesium (PACs5)
[0101] 3.07 g of polyacrylic acid (42.6 mmol monomer units) (weight average molecular weight (M w )=1800Da (Aldrich)) is introduced into a 250ml flask and dissolved in 75ml ultrapure water: the obtained solution is filtered using a microporous filter (pore 45μm). 0.34g of cesium carbonate (Cs2CO3) (2.08 mmoles of cesium) (Aldrich) dissolved in 20ml ultrapure water is added to the filtered solution. Under stirring, the reaction mixture is placed at room temperature (25°C) for 5 minutes, then heated to a temperature of 80°C and maintained at the temperature for 2 hours under stirring to facilitate the removal of the carbon dioxide formed. The solution is placed to cool at room temperature (25°C), filtered again using a microporous filter (pore 45μm) to remove any impurities, and then freeze-dried to obtain 2.85g of partially neutralized polyacrylic acid (as a flaky white solid). The analysis of the sample by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy), performed as described below, shows a cesium content equal to 8.3%, corresponding to about 5% of the neutralized, ie converted into -COO-Cs + The -COOH group.
[0102] ICP-OES analysis (Inductively coupled plasma-optical emission spectroscopy)
[0103] The samples to be analyzed were prepared by acid digestion.
[0104] To this end, 50 mg of partially neutralized polyacrylic acid obtained as described above were placed in a 200 ml flask, to which were added 7.5 ml of nitric acid (65 wt % aqueous solution - Aldrich) and 2.5 ml of sulfuric acid (95 wt % aqueous solution - Aldrich): the resulting mixture was heated to 120° C., maintained at said temperature for 20 hours and subsequently diluted to a volume of 50 ml with ultrapure water. The solution thus obtained was subsequently diluted in nitric acid (HNO3) (1 % aqueous solution obtained by diluting a 65 wt % aqueous solution - Aldrich) in a ratio of 1:10 (v / v) and subsequently analyzed by (inductively coupled plasma-optical emission spectroscopy) (Spectro Genesis, Ametek).
[0105] For each of the two metals analyzed, namely cesium (Cs) and potassium (K), five standard solutions with the following concentrations were used to obtain a calibration curve: 0.05ppm, 0.10ppm, 0.50ppm, 1.00ppm and 5.00ppm. All solutions were obtained by serial dilution starting from two stock solutions of 1000ppm for each metal. A nitric acid (HNO3) solution (a 1% aqueous solution obtained by diluting a 65 wt% Aldrich aqueous solution) was used as a blank.
[0106] The operating conditions used were as follows:
[0107] -Plasma gas flow rate: 0.5L / min;
[0108] -RF power: 1400W;
[0109] - Measurement wavelength: for analyzing cesium (Cs) (wavelength is 455nm), for analyzing potassium (K) (wavelength is 766nm).
[0110] The limit of detection (LOD) was calculated using the background equivalent concentration (BEC) and the signal to background ratio (SBR), and the results were LOD(K) = 0.001 mg / L, LOD(Cs) = 0.003 mg / L.
[0111] Example 2
[0112] Preparation of polyacrylic acid partially neutralized with cesium (PACs10)
[0113] Polyacrylic acid partially neutralized with cesium (PACs10) was prepared by the procedure described in Example 1, the only difference coming from the use of a different amount of cesium carbonate (Cs2CO3).
[0114] For this purpose, 3.07 g of polyacrylic acid (42.6 mmol monomer units) (weight average molecular weight (M w )=1800Da (Aldrich)) was reacted with 0.62g of cesium carbonate (Cs2CO3) (4.16mmoles of cesium) (Aldrich) to obtain 2.98g of partially neutralized polyacrylic acid in the form of a flaky white solid. The sample was analyzed by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy) operated as described in Example 1, showing a cesium content equal to 15.4%, corresponding to about 10% of the neutralized, i.e. converted into -COO-Cs + The -COOH group.
[0115] Example 3
[0116] Preparation of polyacrylic acid partially neutralized with cesium (PACs20)
[0117] Polyacrylic acid partially neutralized with cesium (PACs20) was prepared by the procedure described in Example 1, the only difference coming from the use of a different amount of cesium carbonate (Cs2CO3).
[0118] For this purpose, 3.07 g of polyacrylic acid (42.6 mmol monomer units) (weight average molecular weight (M w )=1800Da (Aldrich)) is reacted with 1.36g of cesium carbonate (Cs2CO3) (8.32mmoles of cesium) (Aldrich) to obtain 3.22g of partially neutralized polyacrylic acid in the form of a flaky white solid. The sample is analyzed by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy) operated as described in Example 1, showing a cesium content equal to 26.7%, which corresponds to about 20% of the neutralized, i.e. converted into -COO-Cs + The -COOH group.
[0119] Example 4
[0120] Preparation of polyacrylic acid partially neutralized with cesium (PACs40)
[0121] Polyacrylic acid partially neutralized with cesium (PACs40) was prepared by the procedure described in Example 1, the only difference coming from the use of a different amount of cesium carbonate (Cs2CO3).
[0122] For this purpose, 3.07 g of polyacrylic acid (42.6 mmol monomer units) (weight average molecular weight (M w)=1800Da (Aldrich)) was reacted with 2.72g of cesium carbonate (Cs2CO3) (16.6mmoles of cesium) (Aldrich) to obtain 3.95g of partially neutralized polyacrylic acid in the form of a flaky white solid. The sample was analyzed by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy) operated as described in Example 1, showing a cesium content equal to 42.1%, which corresponds to about 40% of the neutralized, i.e. converted into -COO-Cs + The -COOH group.
[0123] Example 5
[0124] Preparation of polyacrylic acid partially neutralized with potassium (PAK5)
[0125] Polyacrylic acid partially neutralized with potassium (PAK5) was prepared by the procedure described in Example 1, the only difference coming from the use of a different amount of potassium carbonate (KHCO3).
[0126] For this purpose, 3.07 g of polyacrylic acid (42.6 mmol monomer units) (weight average molecular weight (M w )=1800Da (Aldrich)) was reacted with 0.21g of potassium carbonate (KHCO3) (2.09mmol potassium) (Aldrich) to obtain 2.68g of partially neutralized polyacrylic acid in the form of a flaky white solid. The sample was analyzed by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy) operated as described in Example 1, showing a potassium content equal to 2.2%, which corresponds to about 5% of the neutralized, i.e. converted into -COO-K + The -COOH group.
[0127] Example 6
[0128] Preparation of polyacrylic acid partially neutralized with potassium (PAK10)
[0129] Polyacrylic acid partially neutralized with potassium (PAK10) was prepared by the procedure described in Example 1, the only difference coming from the use of different amounts of potassium carbonate (KHCO3).
[0130] For this purpose, 3.07 g of polyacrylic acid (42.6 mmol monomer units) (weight average molecular weight (M w )=1800Da (Aldrich)) was reacted with 0.42g of potassium carbonate (KHCO3) (4.19mmol potassium) (Aldrich) to obtain 2.98g of partially neutralized polyacrylic acid in the form of a flaky white solid. The sample was analyzed by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy) operated as described in Example 1, showing a potassium content equal to 5%, which corresponds to about 10% of the neutralized, i.e. converted into -COO-K+ The -COOH group.
[0131] Example 7
[0132] Preparation of polyacrylic acid partially neutralized with potassium (PAK20)
[0133] Polyacrylic acid partially neutralized with cesium (PAK20) was prepared by the procedure described in Example 1, the only difference coming from the use of a different amount of potassium carbonate (KHCO3).
[0134] For this purpose, 3.07 g of polyacrylic acid (42.6 mmol monomer units) (weight average molecular weight (M w )=1800Da (Aldrich)) was reacted with 0.84g of potassium carbonate (KHCO3) (8.39mmol potassium) (Aldrich) to obtain 2.68g of partially neutralized polyacrylic acid in the form of a flaky white solid. The sample was analyzed by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy) operated as described in Example 1, showing a potassium content equal to 9.4%, which corresponds to about 20% of the neutralized, i.e. converted into -COO-K + The -COOH group.
[0135] Example 8
[0136] Preparation of polyacrylic acid partially neutralized with potassium (PAK30)
[0137] Polyacrylic acid partially neutralized with cesium (PAK30) was prepared by the procedure described in Example 1, the only difference coming from the use of a different amount of potassium carbonate (KHCO3).
[0138] For this purpose, 3.07 g of polyacrylic acid (42.6 mmol monomer units) (weight average molecular weight (M w )=1800Da (Aldrich)) was reacted with 1.26g of potassium carbonate (KHCO3) (12.59mmol potassium) (Aldrich) to obtain 2.68g of partially neutralized polyacrylic acid in the form of a flaky white solid. The sample was analyzed by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy) operated as described in Example 1, showing a potassium content equal to 12.3%, which corresponds to about 30% of the neutralized, i.e. converted into -COO-K + The -COOH group.
[0139] Example 9
[0140] Making perovskite-based solar cells
[0141] For this purpose, a glass substrate (size 15×15×1 mm; surface resistance equal to 12 Ω / cm2) coated with ITO indium tin oxide (Kintec Kt18086-1) and patterned was used. 2 ) on a glass substrate that had been previously subjected to a cleaning step, including manual cleaning, wiping with a lint-free cloth soaked in a detergent diluted with deionized water. The substrate was then rinsed with deionized water. Subsequently, the substrate was thoroughly cleaned by the following sequential method: an ultrasonic bath in (i) deionized water plus detergent (followed by manual drying with a lint-free cloth); (ii) distilled water [followed by manual drying with a lint-free cloth]; (iii) acetone (Aldrich); and (iv) isopropanol (Aldrich). Specifically, the substrate was placed in a beaker containing a solvent, placed in an ultrasonic bath, maintained at 40°C, and treated for 10 minutes. After treatments (iii) and (iv), the substrate was dried with a compressed nitrogen stream.
[0142] Subsequently, the glass / ITO was further cleaned by treatment in an ozone apparatus (UV ozone cleaning system EXPO3 - Astel) before proceeding immediately to the next step.
[0143] The substrate thus treated is ready for the deposition of a layer based on a hole transport material (hole transport layer - HTL). For this purpose, a solution of poly[bis(4-butylphenyl)diphenylbenzidine (polyTPD) (Aldrich) in chlorobenzene (purity 99.5% - Aldrich) at a concentration equal to 1.5 mg / ml is deposited by spin coating operation at a rotation speed of 4000 rpm (acceleration equal to 500 rpm / s) for 60 seconds: everything is thermally treated (annealed) at 110° C. for 30 minutes. The thickness of the layer based on a hole transport material (hole transport layer - HTL) is found to be equal to 40 nm.
[0144] The material for improving wettability is deposited on the substrate thus obtained. For this purpose, a solution of poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)] (PFN) (Aldrich) in methanol (purity 99.5% - Aldrich) with a concentration of 0.1 mg / ml is deposited by spin coating at a rotation speed of 5000 rpm (acceleration equal to 1000 rpm / s) for 40 seconds, and the whole is then heat treated (annealed) at 100° C. for 5 minutes.
[0145] Subsequently, the obtained substrate is placed in a drying oven and a layer of methylammonium lead iodide (CH3NH3PbI3) obtained in Example 1 and polyacrylic acid (PACs5) partially neutralized with cesium is deposited on top of the layer based on the material for improving wettability, as follows. For this purpose, lead iodide (PbI2) (ultra-dry purity 99.999% - Alfa Aesar) (350.5 mg - 0.76 mmol), methylammonium iodide (MAI) (CH3NH3I) (Great Cell Solar) (120.8 mg-0.76 mmol) and polyacrylic acid (PACs5) partially neutralized with cesium (23.6 mg) were dissolved in anhydrous dimethyl sulfoxide (purity 99.9%-Aldrich) (1 ml), and stirred at 80°C for 3 hours to obtain a product containing 30 wt% of perovskite precursor and 1.5 wt% of polyacrylic acid (PACs5) partially neutralized with cesium (i.e., relative to other solid components (i.e., lead iodide (PbI2) + methyl iodide)). A solution of 5% by weight of polyacrylic acid (PACs5) partially neutralized with cesium (5% by weight of total weight of ammonium (MAI) (CH3NH3I) was prepared. The solution thus obtained was deposited on the layer based on the material for improving wettability by a spin coating operation at a rotation speed equal to 5000 rpm (acceleration equal to 1000 rpm / s) for 20 seconds, and the whole was thermally treated (annealed) at 100° C. for 20 minutes. The thickness of the perovskite and polyacrylic acid (PAA) layer was found to be 325 nm.
[0146] The substrate thus obtained is ready for the deposition of a layer based on an electron transport material (electron transport layer—ETL). To this end, [6,6]-phenyl-C 61 -Methyl butyrate (PC 61 Deposition was carried out from a filtered solution of 1,2-dichloro- ...
[0147] The substrate thus obtained is prepared for the deposition of a layer based on a hole blocking material (hole blocking layer - HBL). For this purpose, a solution of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (Batocuproine-BCP) (96% purity - Aldrich) (9 mg) obtained by a stirring operation at 80° C. for 3 hours in anhydrous isopropanol (99.5% purity - Aldrich) (18 ml) is deposited by a spin coating operation at a rotation speed equal to 6000 rpm (acceleration equal to 1000 rpm / s) for 20 seconds, the substrate obtained being left to stand at room temperature (25° C.) for 5 minutes. The thickness of the layer based on a hole blocking material (hole blocking layer - HBL) is found to be equal to 5 nm.
[0148] Subsequently, a back contact (cathode) in metallic aluminum (Al) was deposited on said layer based on hole blocking material (hole blocking layer—HBL) by evaporation. For this purpose, a Kurt J. Lesker evaporator was used at a temperature equal to 2×10 -6 mmHg pressure and a velocity equal to 0.1 angstrom / second, appropriately covering the area of the solar cell in order to obtain a velocity equal to 4 mm 2 The thickness of the back contact (cathode) in metallic aluminum (Al) was found to be equal to 50 nm.
[0149] The thickness was measured using a Jeol 7600f scanning electron microscope (SEM) equipped with a field emission electron gun, operating at an accelerating voltage of 1 kV to 5 kV and utilizing the signal from the secondary electrons.
[0150] The electrical properties of the perovskite-based solar cells thus obtained were characterized at room temperature (25°C). The current-voltage density (JV) curves were obtained with a 2400 digital multimeter. The photocurrent was measured by exposing the solar cell to the light of a Newport 91160A solar simulator (Newport Corp), which was placed at a distance of 10 mm from the solar cell and equipped with a 300 W xenon light source, using an illumination equal to 100 mm x 100 mm: Table 1 shows the characterization parameters as average values.
[0151] The light intensity was calibrated using a standard silicon solar cell (VLSI Standards - SRC-100-RTD-KG5).
[0152] Specifically, Table 1 shows in order: the reference example number; the composition of the photoactive layer of perovskite and partially neutralized polyacrylic acid; FF (fill factor); Voc (open circuit voltage); Jsc (short circuit photocurrent density); PCE (power conversion efficiency).
[0153] Example 10
[0154] Making perovskite-based solar cells
[0155] Perovskite-based solar cells were obtained using the same procedure reported in Example 9, the only difference coming from the use of perovskite precursors and partially neutralized polyacrylic acid containing different amounts of cesium.
[0156] To this end, lead iodide (PbI2) (ultra-dry purity 99.999% - Alfa Aesar) (350.5 mg - 0.76 mmol), methylammonium iodide (MAI) (CH3NH3I) (GreatCell Solar) (120.8 mg - 0.76 mmol) and the polyacrylic acid partially neutralized with cesium (PACs10) obtained in Example 2 (23.6 mg) were dissolved in anhydrous dimethyl sulfoxide (purity 99.9% - Aldrich) (1 ml), and stirred at 80°C for 3 hours to obtain a solution containing 30 wt% of perovskite precursor and 1.5 wt% of polyacrylic acid partially neutralized with cesium (PACs10) (i.e., 5 wt% of polyacrylic acid partially neutralized with cesium relative to the total weight of other solid components (i.e., lead iodide (PbI2) + methylammonium iodide (MAI) (CH3NH3I)).
[0157] The electrical characterization of the obtained perovskite-based solar cells was performed as described above: In Table 1, the characterization parameters are reported as average values.
[0158] Embodiment 11
[0159] Making perovskite-based solar cells
[0160] Perovskite-based solar cells were obtained using the same procedure reported in Example 9, the only difference coming from the use of perovskite precursors and partially neutralized polyacrylic acid containing different amounts of cesium.
[0161] To this end, lead iodide (PbI2) (ultra-dry purity 99.999% - Alfa Aesar) (350.5 mg - 0.76 mmol), methylammonium iodide (MAI) (CH3NH3I) (GreatCell Solar) (120.8 mg - 0.76 mmol) and the polyacrylic acid partially neutralized with cesium (PACs20) (23.6 mg) obtained in Example 3 were dissolved in anhydrous dimethyl sulfoxide (purity 99.9% - Aldrich) (1 ml), and stirred at 80°C for 3 hours to obtain a solution containing 30 wt% of perovskite precursor and 1.5 wt% of polyacrylic acid partially neutralized with cesium (PACs20) (i.e., 5 wt% of polyacrylic acid partially neutralized with cesium relative to the total weight of other solid components (i.e., lead iodide (PbI2) + methylammonium iodide (MAI) (CH3NH3I)).
[0162] The electrical characterization of the obtained perovskite-based solar cells was performed as described above: In Table 1, the characterization parameters are reported as average values.
[0163] Example 12
[0164] Making perovskite-based solar cells
[0165] Perovskite-based solar cells were obtained using the same procedure reported in Example 9, the only difference coming from the use of perovskite precursors and partially neutralized polyacrylic acid containing different amounts of cesium.
[0166] To this end, lead iodide (PbI2) (ultra-dry purity 99.999% - Alfa Aesar) (350.5 mg - 0.76 mmol), methylammonium iodide (MAI) (CH3NH3I) (GreatCell Solar) (120.8 mg - 0.76 mmol) and the polyacrylic acid partially neutralized with cesium (PACs40) (23.6 mg) obtained in Example 4 were dissolved in anhydrous dimethyl sulfoxide (purity 99.9% - Aldrich) (1 ml), and stirred at 80°C for 3 hours to obtain a solution containing 30 wt% of perovskite precursor and 1.5 wt% of polyacrylic acid partially neutralized with cesium (PACs40) (i.e., 5 wt% of polyacrylic acid partially neutralized with cesium, relative to the total weight of other solid components (i.e., lead iodide (PbI2) + methylammonium iodide (MAI) (CH3NH3I)).
[0167] The electrical characterization of the obtained perovskite-based solar cells was performed as described above: In Table 1, the characterization parameters are reported as average values.
[0168] Table 1
[0169]
[0170] (1) : Fill factor;
[0171] (2) : open circuit voltage;
[0172] (3) : short-circuit photocurrent density;
[0173] (4) : Power conversion efficiency;
[0174] (5) : methylammonium lead iodide [(CH3NH3)PbI3] [(the brackets are the weight % of the perovskite precursor (i.e., lead iodide (PbI2) + methylammonium iodide (MAI) (CH3NH3I))];
[0175] (6) : Partially neutralized polyacrylic acid (the percentage by weight of partially neutralized polyacrylic acid relative to the total weight of other solid components [i.e., lead iodide (PbI2) + methylammonium iodide (MAI) (CH3NH3I)] is shown in brackets).
[0176] From the data reported in Table 1, it can be seen that the perovskite-based solar cells of the present invention have both good power conversion efficiency (PCE) (i.e., PCE>10%) and good electrical properties, i.e., good values of FF (fill factor), Voc (open circuit voltage); and Jsc (short circuit photocurrent density).
[0177] Example 13
[0178] Making perovskite-based solar cells
[0179] Perovskite based solar cells were obtained using the same procedure reported in Example 9, the only differences coming from the use of perovskite precursors and polyacrylic acid partially neutralized with potassium.
[0180] To this end, lead iodide (PbI2) (ultra-dry purity 99.999% - Alfa Aesar) (350.5 mg - 0.76 mmol), methylammonium iodide (MAI) (CH3NH3I) (GreatCell Solar) (120.8 mg - 0.76 mmol) and the polyacrylic acid (PAK5) partially neutralized with potassium obtained in Example 5 (23.6 mg) were dissolved in anhydrous dimethyl sulfoxide (purity 99.9% - Aldrich) (1 ml), and stirred at a temperature of 80°C for 3 hours to obtain a solution containing 30 wt% of perovskite precursor and 1.5 wt% of polyacrylic acid (PAK5) partially neutralized with potassium (i.e., 5 wt% of polyacrylic acid (PAK5) partially neutralized with potassium relative to the total weight of other solid components (i.e., lead iodide (PbI2) + methylammonium iodide (MAI) (CH3NH3I)).
[0181] The electrical characterization of the obtained perovskite-based solar cells was performed as described above: In Table 2, the characterization parameters are reported as average values.
[0182] Specifically, Table 2 shows in order: the reference example number; the composition of the photoactive layer of perovskite and partially neutralized polyacrylic acid; FF (fill factor); Voc (open circuit voltage); Jsc (short circuit photocurrent density); PCE (power conversion efficiency).
[0183] Embodiment 14
[0184] Making perovskite-based solar cells
[0185] Compared to Example 13, perovskite-based solar cells were obtained using the same procedure as reported in Example 9, the only difference coming from the use of perovskite precursors and partially neutralized polyacrylic acid containing different amounts of potassium.
[0186] To this end, lead iodide (PbI2) (ultra-dry purity 99.999% - Alfa Aesar) (350.5 mg - 0.76 mmol), methylammonium iodide (MAI) (CH3NH3I) (GreatCell Solar) (120.8 mg - 0.76 mmol) and the polyacrylic acid (PAK10) partially neutralized with potassium obtained in Example 6 (23.6 mg) were dissolved in anhydrous dimethyl sulfoxide (purity 99.9% - Aldrich) (1 ml), and stirred at a temperature of 80°C for 3 hours to obtain a solution containing 30 wt% of perovskite precursor and 1.5 wt% of polyacrylic acid (PAK10) partially neutralized with potassium (i.e., 5 wt% of polyacrylic acid (PAK10) partially neutralized with potassium relative to the total weight of other solid components (i.e., lead iodide (PbI2) + methylammonium iodide (MAI) (CH3NH3I)).
[0187] The electrical characterization of the obtained perovskite-based solar cells was performed as described above: In Table 2, the characterization parameters are reported as average values.
[0188] Embodiment 15
[0189] Making perovskite-based solar cells
[0190] Perovskite-based solar cells were obtained using the same procedure reported in Example 9, the only differences coming from the use of perovskite precursors and partially neutralized polyacrylic acid containing different amounts of potassium (compared to Example 13) and having different concentrations relative to the total weight of the other solid components, namely lead iodide (PbI2) + methylammonium iodide (MAI) (CH3NH3I).
[0191] To this end, lead iodide (PbI2) (ultra-dry purity 99.999% - Alfa Aesar) (350.5 mg - 0.76 mmol), methylammonium iodide (MAI) ((CH3NH3I)) (GreatCell Solar) (120.8 mg - 0.76 mmol) and the polyacrylic acid (PAK5) partially neutralized with potassium obtained in Example 5 (47.2 mg) were dissolved in anhydrous dimethyl sulfoxide (purity 99.9% - Aldrich) (1 ml), and stirred at a temperature of 80°C for 3 hours to obtain a solution containing 30 wt% of perovskite precursor and 3.0 wt% of polyacrylic acid (PAK5) partially neutralized with potassium (i.e., 10 wt% of polyacrylic acid (PAK5) partially neutralized with potassium relative to the total weight of other solid components (i.e., lead iodide (PbI2) + methylammonium iodide (MAI) (CH3NH3I))).
[0192] The electrical characterization of the obtained perovskite-based solar cells was performed as described above: In Table 2, the characterization parameters are reported as average values.
[0193] Table 2
[0194]
[0195] (1) : Fill factor;
[0196] (2) : open circuit voltage;
[0197] (3) : short-circuit photocurrent density;
[0198] (4) : Power conversion efficiency;
[0199] (5) : methylammonium lead iodide [(CH3NH3)PbI3] [(the weight percentage of the perovskite precursor in brackets (i.e., lead (PbI2) + methylammonium iodide (MAI) (CH3NH3I)]);
[0200] (6) : Partially neutralized polyacrylic acid (the percentage by weight of partially neutralized polyacrylic acid relative to the total weight of other solid components [i.e., lead iodide (PbI2) + methylammonium iodide (MAI) (CH3NH3I)] is shown in brackets).
[0201] As can be seen from the data reported in Table 2, the perovskite-based solar cells of the present invention show good power conversion efficiency (PCE) (i.e., PCE>10%), as well as good electrical properties, i.e., good values of FF (fill factor), Voc (open circuit voltage); and Jsc (short circuit photocurrent density).
Claims
1. A photovoltaic cell (or solar cell) based on perovskite, wherein the perovskite photoactive layer comprises at least one partially neutralized polyacrylic acid in an amount greater than or equal to 3 wt. %, preferably 4 wt. % to 15 wt. %, more preferably 4.5 wt. % to 12 wt. %, relative to the total weight of the perovskite precursor.
2. The perovskite-based photovoltaic cell (or solar cell) according to claim 1, wherein the perovskite is selected from organometallic trihalides having the general formula ABX3, wherein: -A represents a monovalent organic cation, such as methylammonium (CH3NH3 + ), formamidine [CH(NH2)2 + ], n-butylammonium (C4H 12 N + ), tetrabutylammonium (C 16 H 36 N + ), or a mixture thereof; or A represents a monovalent inorganic cation, such as a cesium ion (Cs + ), rubidium ions (Rb + ), potassium ion (K + ), lithium ion (Li + ), sodium ion (Na + ), copper ions (Cu + ), silver ions (Ag + ), or a mixture thereof; or a mixture thereof; -B represents a divalent metal cation, such as lead ion (Pb 2+ ), tin ions (Sn 2+ ), or a mixture thereof; -X represents a halogen anion, such as an iodide ion (I - ), chloride ion (Cl - ), bromide ion (Br - ), or a mixture thereof.
3. A perovskite-based photovoltaic cell (or solar cell) according to claim 1 or 2, wherein the perovskite is selected from the following: methylammonium lead iodide (CH3NH3PbI3), methylammonium lead bromide (CH3NH3PbBr3), methylammonium lead chloride (CH3NH3PbCl3), methylammonium lead bromide iodide (CH3NH3PbI x Br 3-x ), methylammonium lead chloride iodide (CH3NH3PbI x Cl 3-x ), formamidine lead iodide [CH(NH2)2PbI3], formamidine lead bromide [CH(NH2)2PbBr3], formamidine lead chloride [CH(NH2)2PbCl3], formamidine lead bromide iodide [CH(NH2)2PbI x Br 3-x ]、Formamidine lead chloride iodide [CH(NH2)2PbI x Cl 3-x ]、Methylammonium formamidinium lead iodide [(CH3NH3) x (CH(NH2)2) 1-x PbI3], methylammonium formamidinium lead bromide [(CH3NH3) x (CH(NH2)2) 1-x PbBr3], methylammonium formamidinium lead chloride [(CH3NH3) x (CH(NH2)2) 1-x PbCl3], methylammonium formamidinium chloride lead iodide [(CH3NH3) x (CH(NH2)2) 1- x PbI 3-y Cl y ], methylammonium formamidinium bromide lead iodide [(CH3NH3) x (CH(NH2)2) 1-x PbI 3-y Br y ], n-butylammonium lead iodide (C4H 12 NH3PbI3), tetrabutylammonium lead iodide (C 16 H 36 NPbI3), n-butylammonium lead bromide (C4H 12 NH3PbBr3), tetrabutylammonium lead bromide (C 16 H 36 NPbBr3), cesium lead iodide (CsPbI3), rubidium lead iodide (RbPbI3), potassium lead iodide (KPbI3), methylammonium cesium lead iodide [Cs x (CH3NH3) 1-x PbI3], methylammonium potassium lead iodide [K x (CH3NH3) 1-x PbI3], methylammonium chloride cesium lead iodide [Cs x (CH3NH3) 1-x PbI 3-y Cl y ], cesium lead formamidine iodide [Cs x (CH(NH2)2) 1-x PbI3], cesium lead bromide [Cs x (CH(NH2)2) 1-x PbBr3], cesium lead iodide [Cs x (CH(NH2)2) 1-x PbI 3-y Cl y ], methylammonium tin iodide (CH3NH3SnI3), methylammonium tin bromide (CH3NH3SnBr3), methylammonium tin bromide iodide (CH3NH3SnI x Br 3-x ), formamidine tin iodide [CH(NH2)2SnI3], formamidine tin bromide iodide (CH3NH3SnI x Br 3-x ), n-butylammoniumtiniodide (C4H 12 NH3SnI3), tetrabutylammoniumtin iodide (C 16 H 36 NSnI3), n-butylammoniumtin bromide (C4H 12 NH3SnBr3), tetrabutylammoniumtin bromide (C 16 H 36 NSnBr3), methylammonium tin lead iodide (CH3NH3Sn x Pb 1-x I3), tin lead iodide [CH(NH2)2Sn x Pb 1-x I3], or a mixture thereof; preferably selected from: methylammonium lead iodide (CH3NH3PbI3), formamidine lead iodide [CH(NH2)2PbI3], methylammonium formamidine lead iodide chloride [(CH3NH3) x (CH(NH2)2) 1-x PbI 3-y Cl y ], methylammonium chloride cesium lead iodide [Cs x (CH3NH3) 1-x PbI 3- y Cl y ], cesium lead iodide chloride [Cs x (CH(NH2)2) 1-x PbI 3-y Cl y ]; more preferably methylammonium lead iodide (CH3NH3PbI3).
4. A perovskite-based photovoltaic cell (or solar cell) according to any one of the preceding claims, wherein the polyacrylic acid has the general formula (I): in: - n and m are integers, and: - the sum n+m is from 10 to 60000, preferably from 15 to 15000, more preferably from 20 to 6000; - the ratio n:m is from 99:1 to 1:99, preferably from 98:2 to 20:80, more preferably from 95:5 to 50:50; -M + represents a monovalent metal cation selected from alkali metals such as lithium ion (Li + ), sodium ion (Na + ), potassium ion (K + ), rubidium ion (Rb + ), cesium ion (Cs + ), preferably lithium ion (Li + ), potassium ion (K + ), rubidium ion (Rb + ), cesium ion (Cs + ), more preferably potassium ion (K + ), cesium ion (Cs + ); or selected from other monovalent metals such as copper ions (Cu + ), silver ions (Ag + ), gold ions (Au + ), mercury ion (Hg + ), thallium ion (Tl + ), preferably copper ions (Cu + ), silver ions (Ag + ); - or M + represents a monovalent cation having the general formula (II): in: -E represents a nitrogen atom or a phosphorus atom, preferably a nitrogen atom; - R1, R2, R3 and R4 are the same or different from each other and represent a hydrogen atom; or are selected from a linear or branched, saturated or unsaturated C1-C 20 , preferably C1-C 12 , an alkyl group optionally containing a heteroatom; an optionally substituted aryl group; an optionally substituted heteroaryl group; an optionally substituted cycloalkyl group; an optionally substituted heterocyclic group; - or R1 and R2, and / or R2 and R3, and / or R3 and R4, and / or R4 and R1, may be bonded together so as to form, together with the other atoms to which they are bonded, a saturated, unsaturated or aromatic ring containing 2 to 12 carbon atoms, optionally substituted by: a linear or branched, saturated or unsaturated C1-C 20 , preferably C1-C 12 , an alkyl group optionally containing heteroatoms, an optionally substituted aryl group, an optionally substituted heteroaryl group, an optionally substituted cycloalkyl group, an optionally substituted heterocyclic group, a trialkyl-silyl group or a triaryl-silyl group, a dialkyl-amino group or a diaryl-amino group, a dialkyl-phosphinyl group or a diaryl-phosphinyl group, a C1-C 20 , preferably C2-C 10 , linear or branched, saturated or unsaturated alkyl, optionally substituted aryloxy, optionally substituted thioalkoxy or thioaryloxy, cyano, the ring optionally containing heteroatoms such as oxygen, sulfur, nitrogen, silicon, phosphorus, selenium, preferably oxygen, nitrogen; - or M + represents a monovalent cation having the general formula (III): in: - R5 represents a hydrogen atom; or represents a halogen atom such as fluorine, chlorine, bromine, iodine, preferably fluorine, chlorine; or selected from linear or branched, saturated or unsaturated C1-C 20 , preferably C1-C 12 , optionally containing heteroatoms alkyl; optionally substituted aryl; optionally substituted heteroaryl; optionally substituted cycloalkyl; optionally substituted heterocyclic group; preferably R5 is hydrogen or methyl; - R6, R7, R8 and R9 are the same or different from each other and represent a hydrogen atom; or are selected from a linear or branched, saturated or unsaturated C1-C 20 , preferably C1-C 12 , an alkyl group optionally containing a heteroatom; an optionally substituted aryl group; an optionally substituted heteroaryl group; an optionally substituted cycloalkyl group; an optionally substituted heterocyclic group; - or R7 and R8, and / or R9 and R 10 may be bonded together so as to form, together with the other atoms to which they are bonded, a saturated, unsaturated or aromatic ring containing 2 to 12 carbon atoms, optionally substituted by: a straight or branched, saturated or unsaturated C1-C 20 , an alkyl group optionally containing heteroatoms, an optionally substituted aryl group, an optionally substituted heteroaryl group, an optionally substituted cycloalkyl group, an optionally substituted heterocyclyl group, a trialkylsilyl group or a triaryl-silyl group, a dialkyl-amino group or a diaryl-amino group, Dialkyl-phosphinic acid group or diaryl-phosphinic acid group, C1-C 20 , preferably C2-C 10 , a linear or branched, saturated or unsaturated alkoxy group, an optionally substituted aryloxy group, an optionally substituted thioalkoxy group or thioaryloxy group, a cyano group, the ring optionally containing heteroatoms, such as oxygen, sulfur, nitrogen, silicon, phosphorus, selenium, preferably oxygen, nitrogen; preferably, R6, R7, R8 and R9 represent hydrogen atoms.
5. The perovskite-based photovoltaic cell (or solar cell) according to any one of the preceding claims, wherein in the partially neutralized polyacrylic acid, free carboxyl groups are present in an amount of 1% to 99%, preferably 20% to 98%, more preferably 50% to 96%, relative to the total amount of carboxyl groups present in the polyacrylic acid.
6. A perovskite-based photovoltaic cell (or solar cell) according to any one of the preceding claims, wherein the weight average molecular weight (M w ) is 700 Da to 4,000,000 Da, preferably 1,000 Da and 1,000,000 Da, more preferably 1,500 Da and 400,000 Da.
7. A perovskite-based photovoltaic cell (or solar cell) according to any one of the preceding claims, comprising: - a glass substrate coated with a transparent conductive oxide layer (transparent conductive oxide—TCO) constituting the anode, typically fluorine-doped tin oxide (SnO2:F) (FTO) or indium tin oxide (ITO); - a layer based on a hole transport material (hole transport layer—HTL), preferably a layer of poly[bis(4-butylphenyl)-diphenylbenzidine] (polyTPD); - optionally, a layer based on a material for improving wettability, preferably a layer of poly[9,9-bis(3'-(N,N-dimethyl)-N-ethylammonium-propyl-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)] diiodide (PFN-I) or a layer of poly[9,9-bis(3'-(N,N-dimethyl)-N-ethylammonium-propyl-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)] (PFN); - a photoactive layer comprising: at least one perovskite, preferably methylammonium lead iodide (CH3NH3PbI3) [methylammonium lead iodide (CH3NH3PbI3) is the most commonly used structure due to its high absorption coefficient throughout the UV and visible spectral range, a band gap equal to 1.57 eV, close to the optimum value for maximizing the conversion efficiency and a considerable diffusion distance (more than 100 nm) for electrons and electron holes (or holes)]; and at least one partially neutralized polyacrylic acid, preferably partially neutralized with cesium or potassium, the amount of free carboxyl groups of which is between 60% and 95%; - a layer based on an electron transport material (electron transport layer - ETL), preferably [6,6]-phenyl-C 61 -Methyl butyrate (PC 61 BM) layer; - Optionally, a layer based on a hole-blocking material (hole-blocking layer—HBL), preferably a layer of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (Batocuproin—BCP) or ethoxylated polyethyleneimine (PEIE); A metal contact, called back contact, which constitutes the cathode, preferably a layer of gold, silver or metallic aluminum.
8. A perovskite-based photovoltaic cell (or solar cell) according to any of the preceding claims, wherein the electrical energy generated by the at least one perovskite-based photovoltaic cell (or solar cell) is transmitted using a wiring system connected to the perovskite-based photovoltaic cell (or solar cell).
9. A method for preparing a perovskite-based photovoltaic cell (or solar cell), comprising the following steps: (a) preparing a glass substrate coated with a transparent conductive oxide layer (transparent conductive oxide-TCO) (anode); (b) depositing a layer based on a hole transport material (hole transport layer - HTL) on the substrate obtained in step (a); (c) optionally, depositing a layer based on a material for improving wettability on the layer based on a hole transport material (hole transport layer—HTL) obtained in step (b); (d) preparing a mixture comprising a perovskite precursor and at least one partially neutralized polyacrylic acid, said partially neutralized polyacrylic acid being present in said mixture in an amount greater than or equal to 3% by weight, preferably from 4% to 15% by weight, more preferably from 4.5% to 12% by weight, relative to the total weight of the perovskite precursor; (e) depositing the mixture obtained in step (d) on the layer based on a hole transport material (hole transport layer—HTL) obtained in step (b) or on the layer based on a material for improving wettability obtained in step (c) to obtain a photoactive layer; (f) depositing a layer based on an electron transport material (electron transport layer - ETL) on the photoactive layer obtained in step (e); (g) optionally, depositing a layer based on a hole blocking material (hole blocking layer - HBL) on the layer based on an electron transport material (electron transport layer - ETL) obtained in step (f); (h) depositing a metal contact constituting the cathode, called back contact, on the layer based on an electron transport material (electron transport layer—ETL) obtained in step (f) or on the layer based on a hole blocking material (hole blocking layer—HBL) obtained in step (g); Wherein said steps (b), (c), (e), (f) and (g) are carried out at a temperature below 120°C, preferably 20°C to 115°C.
10. Use of the perovskite-based photovoltaic cell (or solar cell) according to any of the preceding claims in: building integrated photovoltaic systems (building integrated photovoltaics - BIPV); photovoltaic windows; greenhouses; photobioreactors; noise barriers; lighting engineering; design; advertising; automotive industry.
11. A composition comprising at least one perovskite and at least one partially neutralized polyacrylic acid, wherein the amount of the at least one partially neutralized polyacrylic acid is greater than or equal to 3% by weight, preferably from 4% to 15% by weight, more preferably from 4.5% to 12% by weight, relative to the total weight of the perovskite precursor.
12. The composition according to claim 11, wherein the perovskite is selected from those according to claim 2 or 3, and the partially neutralized polyacrylic acid is selected from those according to any one of claims 4 to 6.